Glauben lehren: Festschrift für Wolfgang Schoberth zum 65. Geburtstag - Hamilton, Nadine; Hamilton, Stephen James; Hailer, Martin (Evangelische Verlagsanstalt, 2023)
Is it possible to "teach faith"? Hardly: for faith is an event of God's creative presence. Rather, there is something to teach and to learn in faith, as well for the sake of it. This is the noblest task of dogmatics, which can be called "the teachings of the faith" - but also simply "teaching faith". Rightly understood, such teachings of the faith are not a finished product to be memorized, but instead present a hermeneutical approach to the various subjects and questions involved in faith. In this spirit, the present volume presents studies on major topics in dogmatics and arranges them according to the classical loci scheme. Here, however, this task is not undertaken only by one systematic theologian, or even a group of systematic theologians, but instead by different authors from various theological disciplines. This interdisciplinary approach produces a conceptual creativity which characterises this book and is crucial for the process of "teaching faith" in general.